GIS-Based Multi-Criteria Flood Hazard Mapping Using a Scoring and Weighting Approach in Trucuk and Bojonegoro Districts, East Java, Indonesia - Vallery Aldifa Almaushily; Hendrata Wibisana (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Trucuk and Bojonegoro Districts in Bojonegoro Regency, East Java, are low-lying areas that experience recurring inundation whenever the Bengawan Solo River overflows during the rainy season. This study maps flood-prone zones across the two districts using a Geographic Information System (GIS) so that flood risk reduction efforts can be directed more precisely. Four physical parameters known to influence flood occurrence, annual rainfall, slope gradient, soil type, and land use, were each reclassified and assigned a score and weight reflecting their relative contribution to flooding. The four parameter maps were combined through an Intersect overlay in ArcGIS Pro, and the resulting composite scores were divided into five hazard classes using the equal-interval method. The analysis shows that the low hazard class dominates the study area with 2,873 ha (43%), followed by the very high class at 1,557 ha (23%), the high class at 1,141 ha (17%), the very low class at 1,053 ha (16%), and the moderate class at only 81 ha (1%). Slope emerged as the most influential parameter: because flat terrain (0–8%) covers 99% of the study area, this class produced the highest rating value of 27 in the overlay calculation. Interviews conducted in ten villages confirmed that the mapped hazard classes correspond with residents’ actual flooding experience, particularly among settlements located within one kilometre of the Bengawan Solo River. The resulting map is intended to help the Bojonegoro Regional Disaster Management Agency (BPBD) prioritize flood mitigation measures. Contribution to Sustainable Development Goals (SDGs): SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate Action